Needs of parents of very preterm infants in Neonatal Intensive Care Units: A mixed methods study
Objectives To explore needs of parents of very preterm infants hospitalised in Neonatal Intensive Care Units according to their socioeconomic position, obstetric history and infant’s characteristics. Methodology Sequential explanatory mixed methods study. Individual quantitative questionnaires (n = 118 mothers; 89 fathers) during infants’ hospitalisation; couples-based semi-structured interviews (n = 26) four months after childbirth (July 2013–June 2014). Setting All level III public neonatal intensive care units in North Portugal. Results Mothers valued more information needs than fathers and their overall scores were mainly influenced by age and educational level, while fathers’ needs perceptions were influenced by previous children. Despite gender differences, the assurance and proximity needs of parents apply across sociotechnical environments. Qualitative findings added the following needs: instrumental support from the government; regular emotional support from psychologists and social workers; enhancement of privacy to assure family-centred information and comfort; and availability of peers and health professionals as mediators in the provision of coherent information. Conclusions The promotion of family-friendly and gender-equality policies is crucial to support family integrated healthcare services. This study raises awareness for developing sensitive conceptual frameworks and instruments to assess parents’ needs considering their socioeconomic position and reproductive trajectories, as well as privacy and regular emotional support in the neonatal intensive care unit.